2016
DOI: 10.1186/s13034-016-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of factors impacting resilience among youth in post-conflict Liberia

Abstract: BackgroundIn 2008, 5 years after the Liberian civil war ended, there were an estimated 340,000 orphans in Liberia, 18 % of the total child population of the country. Given that children make up half the population and that these children experienced significant trauma and loss both through direct exposure to the war and then to the Ebola epidemic, and indirectly as a result of the trauma experienced by their parents, the recovery of these children is essential to the recovery of the nation as a whole. The goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 21 publications
3
51
0
4
Order By: Relevance
“… [ 85 ] LaFromboise et al, 2006; ( n = 212); US Aboriginal youth (10–15 years) Resilience is conceptualized as a protective mechanism that modifies an individual’s response to risk situations and operates at critical points during one’s life (Newcomb, 1992). [ 168 ] Levey et al, 2016; ( n = 75); Liberia Youth in post-conflict Liberia (13–18 years) Resilience is defined as evidence of adaptive functioning and psychological health. [ 109 ] Longman-Mills et al, 2013; ( n = 2294); Colombia, El Salvador, Jamaica, Nicaragua, Panama, Uruguay University students with experiences of child abuse Resilience as the ability to help individuals cope with adversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 85 ] LaFromboise et al, 2006; ( n = 212); US Aboriginal youth (10–15 years) Resilience is conceptualized as a protective mechanism that modifies an individual’s response to risk situations and operates at critical points during one’s life (Newcomb, 1992). [ 168 ] Levey et al, 2016; ( n = 75); Liberia Youth in post-conflict Liberia (13–18 years) Resilience is defined as evidence of adaptive functioning and psychological health. [ 109 ] Longman-Mills et al, 2013; ( n = 2294); Colombia, El Salvador, Jamaica, Nicaragua, Panama, Uruguay University students with experiences of child abuse Resilience as the ability to help individuals cope with adversity.…”
Section: Resultsmentioning
confidence: 99%
“…Braverman ([ 167 ], p. 4) argues that “[resilience] researchers have thus far been more successful in identifying protective factors than in explaining how they operate”. This definitely rings true in the substance use literature, where significantly fewer researchers attempt to conceptualize resilience as a dynamic process, which explores the interactions between risk and protective factors, than those who utilize an outcome or trait-based approach to operationalize resilience [ 79 , 86 , 87 , 102 , 108 , 110 , 113 , 115 , 120 , 124 , 129 , 151 , 152 , 154 , 155 , 168 172 ]. Just under half of these papers are qualitative investigations of resilience, while the rest are quantitative, utilizing resilience models and longitudinal data sets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharing and self-consoling, considered as positive coping mechanisms, were the two most commonly used coping practices and reported to be the most effective. In post-conflict areas such as this, developing resiliency skills could be a key in developing positive mental health [ 49 ]. Studies among vulnerable groups in Nepal have shown that developing resiliency can have better outcomes and is feasible in the context of LMIC settings like Nepal [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilience was defined as evidence of daily functioning, ability to make realistic plans for the future and presentation of an overall consistent and coherent narrative. A number of individual characteristics were found to be protective in the overall study population, including emotion regulation, cognitive flexibility, agency, social intelligence and, in some cases, meaning-making (Levey et al, 2016). Here, we focus specifically on resilience and recovery following the loss of a parent, identify factors that moderate the impact of the loss and consider interventions that could help vulnerable children following the loss of a parent.…”
Section: Introductionmentioning
confidence: 99%